2018
DOI: 10.1007/s00268-018-4633-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with Multidrug‐Resistant Enterobacteriaceae is Associated with Increased Mortality Following Burn Injury in Sub‐Saharan Africa

Abstract: MDR bacteria, especially Enterobacteriaceae, are common and are associated with worse burn injury outcomes. In resource-poor environments, a greater emphasis on prevention of MDR bacterial colonization, improved isolation precautions, affordable diagnostics, and antibiotic stewardship are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…In this study, we investigated the prevalence of vaginal colonization with clinically important AMR bacteria among women in labour at three primary health care facilities in and close to Kampala in central Uganda; and established exposures associated with AMR. The prevalence of colonization with MDR bacteria in our study was 46.6%, similar to those reported from Malawi and Ethiopia [26][27][28]. Although direct comparison of results between studies are complicated by the lack of consensus on how MDR should be defined, we used an internationally acknowledged MDR definition, making our findings comparable to those from similar studies [29,30].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we investigated the prevalence of vaginal colonization with clinically important AMR bacteria among women in labour at three primary health care facilities in and close to Kampala in central Uganda; and established exposures associated with AMR. The prevalence of colonization with MDR bacteria in our study was 46.6%, similar to those reported from Malawi and Ethiopia [26][27][28]. Although direct comparison of results between studies are complicated by the lack of consensus on how MDR should be defined, we used an internationally acknowledged MDR definition, making our findings comparable to those from similar studies [29,30].…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a study from sub-Saharan Africa found that colonisation with MDR Enterobacteriaceae is associated with an increased risk of mortality after burn injury. 27 This finding needs to be interpreted with caution, as the study groups were selected based on exploratory analysis, not as a priori. Additionally, the results were based on the presence of colonisation, not the incidence of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, infections caused by Pseudomonas + Klebsiella and Acinetobacter + Klebsiella have been recognized as the major cause of increased mortality and morbidity among pediatric patients [ 19 , 20 ]. Additionally, burn wound colonization with MDR Enterobacteriaceae has been associated with high mortality in hospitalized children [ 21 ]. However, it is important to note that the etiology and profile of resistance can vary from one healthcare setting to another [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%